SKENARIO IMPLEMENTASI KEBIJAKAN BLUD PADA RUMAH SAKIT UMUM DAERAH OTO ISKANDAR DI NATA KABUPATEN BANDUNG - Yunia, Santi; Trilestari, Endang W.; Listiani, Teni (ADMIT: Jurnal Administrasi Terapan, 2024)
The transformation of Oto Iskandar Di Nata Regional General Hospital (RSUD OTISTA) into a Regional Public Service Agency (BLUD) aims primarily to improve the quality of healthcare services. However, even after becoming a BLUD, the quality of healthcare services provided to the community has not yet reached optimal levels. This study aims to examine the implementation of the BLUD policy at RSUD OTISTA, analyze the factors that hinder the policy's implementation, and formulate a scenario for planning the BLUD policy implementation. The research uses a qualitative case study method combined with Soft Systems Methodology (SSM). Data collection was conducted through interviews, document analysis, and observations. The scenario formulation for BLUD policy implementation was carried out using the TAIDA method and SSM. The study's findings indicate that the main issues in policy implementation are human resources and financial resources. Based on these problems, two scenarios were developed: the human resources and the financial scenario. The best scenarios are human resources scenario I and financial scenario I, which show that the quality of healthcare services will be maximized if supported by professional human resources and sufficient financial resources. To improve employee competence, it is necessary to conduct BLUD socialization, evaluate employee placement, determine the number, type, and qualifications of employees, coordinate with the BKPSDM, and carry out employee selection and recruitment. To increase hospital revenue, it is necessary to develop new tariffs, benchmark tariffs with other hospitals, propose tariff increases, optimize cooperation with insurance companies, and manage insurance claims effectively and efficiently.